It's a wonderful woof ebook - Quinn, Spencer (Chet and Bernie Mystery, 2021)
INSTANT USA TODAY BESTSELLER Spencer Quinn's It's a Wonderful Woof presents a holiday adventure for Chet the dog, "the most lovable narrator in crime fiction" ( Boston Globe ), and his human partner, PI Bernie Little. Holiday time in the Valley, and in the holiday spirit—despite the dismal shape of the finances at the Little Detective Agency—Bernie refers a potential client to Victor Klovsky, a fellow private eye. It's also true that the case—promising lots of online research but little action—doesn't appeal to Bernie, while it seems perfect for Victor, who is not cut out for rough stuff. But Victor disappears in a rough-stuff way, and when he doesn't show up at his mom's to light the Hanukkah candles, she hires Chet and Bernie to find him. They soon discover that Victor's client has also vanished. The trail leads to the ruins of a mission called Nuestra Señora de los Saguaros, dating back to the earliest Spanish explorers. Some very dangerous people are interested in the old mission. Does some dusty archive hold the secret of a previously unknown art treasure, possibly buried for centuries? What does the Flight into Egypt—when Mary, Joseph and the baby Jesus fled Herod—have to do with saguaros, the Sonoran desert cactus? No one is better than Chet at nosing out buried secrets, but before he can, he and Bernie are forced to take flight themselves, chased through a Christmas Eve blizzard by a murderous foe who loves art all too much. At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.